Evaluation of Mung bean Varieties and Production Technologies at Farmer’s Fields in Western Rajasthan - Sharma, N K; Panwar, P K; Kumawat, N (Annals of Arid Zone, 2017)
Eighteen varietal trials accommodating eight varieties and ninety technology demonstrations of mung bean were conducted under rainfed as well as irrigated situations at farmer’s fields during kharif-2015 in six districts of western Rajasthan viz. Jaisalmer, Bikaner, Churu, Jhunjhunu, Hanumangarh and Sriganganagar. The mean seed yield of mung bean varieties ranged between 292 to 515 kg ha-1 under rainfed and 591 to 885 kg ha-1 under irrigated situation. Among varieties, the maximum seed yield of 737 kg ha-1 was produced by GM-4 followed by MH-421, SML-668, RMG-492 and IPM 02-3 with 691, 635, 634 and 618 kg ha-1, respectively. Under technology demonstrations, seed yield of mung bean under rainfed situation varies 250 to 630 kg ha-1 with mean yield of 409 kg ha-1. However, the seed yield under irrigated situation varied from 435 to 1635 kg ha-1 with mean of 981 kg ha-1. The overall productivity of the mung bean demonstrations was found 38.4% higher over average productivity of the Rajasthan